COMPOSITE RCC/FERROCEMENT GRID SLAB - Prof. Dharane S. S.; Prof. Dudhal K. M; Prof. Jagtap T. N. (International Journal of Innovations in Engineering Research and Technology, 2022)
A RCC/FERROCEMENT grid slab wherein the grid beams are made up of hollow circular cross sections of preferably mild steel and hollow slabs are repared by using foreign material like HDPE balls/pods and concrete. The said grid slab has strength, impermeability, light weight, good appearance, reversal load carrying capacity, more moment carrying capacity, more shearing capacity, ductility and can be used for large column free area. The skeletal steel can also be used for beams and slabs in the form of alternate triangular trough, trapezoidal trough, rectangular trough, corrugated trough in both the directions of the slab.The said grid slab which provides fast construction, economical and cost effective along with impartibility and can also be used for residential buildings, public buildings, raft foundations, water tanks, retaining walls etc.